2017
DOI: 10.1080/2162402x.2017.1347742
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive features of tumor-infiltrating γδ T lymphocytes in human colorectal cancer

Abstract: γδ T cells usually infiltrate many different types of cancer, but it is unclear whether they inhibit or promote tumor progression. Moreover, properties of tumor-infiltrating γδ T cells and those in the corresponding normal tissue remain largely unknown. Here we have studied features of γδ T cells in colorectal cancer, normal colon tissue and peripheral blood, and correlated their levels with clinicopathologic hallmarks. Flow cytometry and transcriptome analyses showed that the tumor comprised a highly variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(157 citation statements)
references
References 51 publications
(69 reference statements)
10
143
4
Order By: Relevance
“…41 However, the analysis showed wide variability in the infiltration of tumors by cd T cells. 37,110 Interestingly, though a pan-cancer analysis of the TCGA database identified a combined Th1/Th17 immune signature as the most beneficial for patient survival, this group showed the most pronounced Th17 gene signature but appeared balanced by the presence of a Th1 response. 109 This computational-based identification was later optimised by Tosolini et al, 109 allowing for more accurate assessment of cd TILs from bulk tumor transcriptomes.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…41 However, the analysis showed wide variability in the infiltration of tumors by cd T cells. 37,110 Interestingly, though a pan-cancer analysis of the TCGA database identified a combined Th1/Th17 immune signature as the most beneficial for patient survival, this group showed the most pronounced Th17 gene signature but appeared balanced by the presence of a Th1 response. 109 This computational-based identification was later optimised by Tosolini et al, 109 allowing for more accurate assessment of cd TILs from bulk tumor transcriptomes.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
“…For example, the presence of IL-17producing cd T cells in colon cancer has been associated with poor prognosis. 37,110 Interestingly, though a pan-cancer analysis of the TCGA database identified a combined Th1/Th17 immune signature as the most beneficial for patient survival, this group showed the most pronounced Th17 gene signature but appeared balanced by the presence of a Th1 response. 111 This study requires further dissection to determine the relative contribution of Th1 and Th17 genes to this signature.…”
Section: Applications Of CD T Cells In Immunotherapymentioning
confidence: 99%
“…Different results were obtained analyzing 70 patients affected by CRC . Functional analysis of tumor‐infiltrating γδ T cells demonstrates that both Vδ1 and Vδ2 T cells in CRC and adjacent normal tissues preferentially produce IFN‐γ, but very low IL‐17.…”
Section: γδ and Cancermentioning
confidence: 93%
“…28 In another study, we also have found that T cells are a minor population among colon cancer-infiltrating leukocytes and their abundance correlate with better clinical outcome, indicating that they are probably involved in controlling tumor growth at an early stage of disease. 29 However, a recent analysis of expression signatures from ∼18,000…”
Section: T Cellsmentioning
confidence: 99%
“…With a limited T cell receptor repertoire and evidence indicating that a predominant mode of cell activation is in response to nonpeptidic ligands, cytokines, and signaling via NKG2D and similar receptors [28][29][30][31][32][33][34][35], γδ T cells are implicated as early responders in immune responses and/or as innate-adaptive bridging cells, responding to innate signals to then direct the development of the adaptive immune response via secretion of cytokines and other factors. As a population, γδ T cells can exert inflammatory/cytotoxic [36,37] or immuno-regulatory effector functions [38,39], are integral to the control of infections [40,41], and can exhibit potent anti-tumor activity [42][43][44]. The role of γδ T cells in HIV viral pathogenesis is unclear to date; shifts in γδ T cell subsets defined by T cell receptor usage (Vδ1 and Vδ2) occur early in infection [45] due to a substantial loss of the Vγ2-Jγ1.2/Vδ2+ subset that is not always recovered with viral suppression [46].…”
Section: Introductionmentioning
confidence: 99%